Editorial: Promoting the use of bio-fertilizers to improve soil health - Shaaban, Muhammad; Asgari Lajayer, Behnam; Nazir, Gazala (Frontiers in Agronomy, 2025)
Graphical AbstractIllustration depicting a farmer applying bio-fertilizers to enhance soil health. A beaker with bio-fertilizers and microbial consortia lead to improved soil condition. Circular bio-economy is signified by crops and a green cycle arrow, indicating sustainability. Labels include “BIO-FERTILIZERS,” “MICROBIAL CONSORTIA,” “CIRCULAR BIO-ECONOMY,” and “SOIL HEALTH."